A tactual weld seam tracking method in super narrow gap of thick plates - Lei, Ting; Huang, Yu; Shao, Wenjun; Liu, Weinan; Rong, Youmin (Robotics and computer-integrated manufacturing, 2020)
The contact-type displacement and angular sensors were improved and utilized in weld seam trajectory detection. A detection–compensation–tracking system was developed. The mechanical part of this system was installed and independent of the robot, which can realize the detection of right-left deviation and up–down offset of the weld path. In the experiment, the position coordinates of the detection point in weld groove were calculated and weld seam tracking was carried out simultaneously owing to its single control system. When the absolute interpolation algorithm was adopted, the average error of width deviation and depth deviation were 0.1817 mm and 0.1449 mm, respectively. [Display omitted]